Measuring sperm backflow following female orgasm: a new method. (1st January 2016) - King, Robert; Dempsey, Maria; Valentine, Katherine A.
Abstract : Background: Human female orgasm is a vexed question in the field while there is credible evidence of cryptic female choice that has many hallmarks of orgasm in other species. Our initial goal was to produce a proof of concept for allowing females to study an aspect of infertility in a home setting, specifically by aligning the study of human infertility and increased fertility with the study of other mammalian fertility. In the latter case - the realm of oxytocin-mediated sperm retention mechanisms seems to be at work in terms of ultimate function (differential sperm retention) while the proximate function (rapid transport or cervical tenting) remains unresolved. Method: A repeated measures design using an easily taught technique in a natural setting was used. Participants were a small (n=6), non-representative sample of females. The introduction of a sperm-simulant combined with an orgasm-producing technique using a vibrator/home massager and other easily supplied materials. Results: The sperm flowback (simulated) was measured using a technique that can be used in a home setting. There was a significant difference in simulant retention between the orgasm (M=4.08, SD=0.17) and non-orgasm (M=3.30, SD=0.22) conditions; t (5)=7.02, p=0.001. Cohen's d=3.97, effect size r=0.89. This indicates a medium to small effect size. Conclusions: This method could allow females to test an aspect of sexual response that has been linked to lowered fertility in a home setting with minimal training. It needs to be replicated with a larger sample size.